(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This article deals with the normative dimensions of law and morals in the case of practical conflicts (dilemmas and disagreements) in the fields of bioethics and medical deontology. A special attention is paid to the evaluation of the “act and omission doctrine”, as a fundamental framework in the causally based conception of responsibility. An alternative, consequence-based, conception of responsibility will be defended as a part of a consequentialist approach to the problems of ethics.